2022
DOI: 10.1111/papr.13141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cross‐sectional area and fat infiltration of paraspinal muscles on analgesic efficacy of epidural steroid injection in elderly patients

Abstract: Background: An assessment of paraspinal muscle degeneration based on magnetic resonance imaging has been used to investigate both sarcopenia and myosteatosis.The morphologic changes in cross-sectional area and fat infiltration of the paraspinal muscles can affect pain outcomes after epidural steroid injection.Methods: Patients ≥65 years of age who underwent fluoroscopy-guided lumbar epidural steroid injections were enrolled. Good analgesia was defined as ≥50% reduction in pain score at 4 weeks after injection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In the additional analysis stratified by fatty infiltration severity, only age was significantly associated with the severity of multifidus fatty infiltration, which corresponds with the prior study [ 16 ]. Although intramuscular adipose tissues compositionally varied in different body locations depending on sex and BMI [ 42 , 43 ], they did not have a significant association with fatty infiltration severity in this study, which was consistent with the results of a prior lumbar-related study [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the additional analysis stratified by fatty infiltration severity, only age was significantly associated with the severity of multifidus fatty infiltration, which corresponds with the prior study [ 16 ]. Although intramuscular adipose tissues compositionally varied in different body locations depending on sex and BMI [ 42 , 43 ], they did not have a significant association with fatty infiltration severity in this study, which was consistent with the results of a prior lumbar-related study [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…As patients with cervical radiculopathy have significantly larger amounts of fatty infiltration in their muscles compared with healthy controls [ 3 ], this study revealed that high-grade fatty infiltration in the multifidus muscle might have adverse impacts on the response to CIESI in patients with cervical radicular pain. Similarly, a recent study found that high fatty infiltration of the paraspinal muscles in the lumbar area was independently associated with poor response to lumbar epidural steroid injections in patients with lumbar spondylosis [ 8 ]. The underlying mechanisms of multifidus fatty infiltration in spinal disorders are not well-understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we only measured the CSA and did not consider the fat infiltration of the psoas muscles. Changes in muscle function and quality have been emphasized in the diagnosis of sarcopenia recently [ 24 ]. Therefore, further studies about the impact of fat infiltration on PEBN are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although sarcopenia is known to be associated with poor prognosis after lumbar spine surgeries [ 21 , 22 , 23 ], only a few studies exist on sarcopenia’s effect in epidural procedures [ 24 ]. In addition, there is no study on the effect of sarcopenia in patients with LSS who underwent PEBN.…”
Section: Introductionmentioning
confidence: 99%